Selection and Monitoring of Assignments in the Audit of Financial Reporting - О. LUBENCHENKO; S. SHULHA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
Problems related to the quality assessment of completed audit assignments are analyzed. As the increasing number of users take management decisions on the basis of audit reports, independent audit is intended to guarantee a sound verification of financial reporting at company level, which can be achieved through the procedures for the assignment quality control.   The article’s objective is to develop methodical recommendations on quality assessment of individual auditing assignments for auditing firms.An analytical review of the normative criteria for selection of assignments for monitoring is made, and the authors’ criteria based on the risk oriented approach to the assessment of assignments of the financial audit are proposed: (i) obligatory auditing, including the auditing of financial reporting of companies with public significance (50% of the total number of the assignments in obligatory audit); (ii) voluntary audit (at least one assignment of the key partner), with the review of financial reporting covering 10% of the total number of the review assignments; other assignments covering 10% or more of the total number of the assignments on providing reassurance, which is not audit or review; selection of the most risky assignments with high level of the implicit risk; related services covering 10% of the total number of assignments pertaining to related services on agreed procedures and compilation of information (with selecting most complicated issues of business operation, which were subject to concern in providing related services and assignments for a new customer). A four-phase model of the assessment of selected assignments of an auditing firm is elaborated: acceptance of customer and assignment; planning and assessment of risks; assignment completion; formulation of auditor opinion and control actions on quality assurance. The practical implementation of this model involves documenting of the internal control of the quality of audit, analysis of results of the quality control, accumulation of errors and correcting actions at system and assignment level.